Gender Norm in Saudi Arabia Within Takki The Series Directed By Mohammad Makki - Prafitri Haziza; Siti Rohmah Soekarba (Indonesian Journal of Arabic Studies, 2023)
Purpose: This paper aims to reveal gender norms in Takki the series directed by a Saudi director, Mohammad Makki. This series is interesting to analyze because the social and gender problems are based on the social realities in society. Design/ methods/approach: The research is done by using qualitative methods with gender norms as the main focus. The data source used in the research originated from a Netflix serial with audio in Arabic and subtitle text in English and Bahasa Indonesia. To analyze gender norms in Takki the series, the author uses a semiotic approach theory by Charles Peirce and gender norm theories. Findings: The semiotic approach in this research study resulted in two conclusions: Gender norms in Saudi Arabia within Takki the series mostly aimed to rule women in various fields of life and with the new rules made by the government in real life, gender norms that bind women within Takki the series also experiences shifting that eventually made changes in various fields of life as well as enhancement of womenâ€™s right in Saudi Arabia. Research implications: Â This research contributes to the understanding of contemporary Saudi culture and media. It highlights the role of digital media in shaping and reflecting societal attitudes towards gender. By focusing on a locally produced and popular web series, the study underscores the significance of regional media productions in contributing to social discourse and change in the Middle East.This research contributes to the understanding of contemporary Saudi culture and media. It highlights the role of digital media in shaping and reflecting societal attitudes towards gender. By focusing on a locally produced and popular web series, the study underscores the significance of regional media productions in contributing to social discourse and change in the Middle East.